20-line multi-wavelength laser source at 1600nm region with Brilloun/erbium fiber laser - S. W. Harun; H. Ahmad (Indonesian Journal of Physics, 2004)
The operation of the Brillouin/erbium fiber laser (BEFL) in the long wavelength band (L-band) is experimentally demonstrated. The Stokes frequency is shifted 10GHz from its Brillouin pump with a tunability from 1598-1612nm for the single wavelength BEFL. Multiple wavelength generation in the BEFL is realised by adding two 3-dB couplers, which are joined in a reverse-S arrangement to take a portion of the generated BEFL signal and re-inject it into the SMF to seed a cascaded BEFL line in the same direction as the first BEFL line. 20 lines including the anti-Stokes are obtained with a maximum Brillouin pump and 980-nm pump power of 8.8mW and 92mW, respectively. The L-band BEFL has the potential to be used in future wavelength division multiplexing (WDM) communication system.